Extraction of Phenolic Active Compounds from Coffee Leaves (Coffea sp.) Using the Ultrasound-Assisted Extraction Method and Total Phenol Analysis - Nur Aini Dwi Alfinaini; Boy Arief Fachri; Pratamai Shelli; Helda Wika Amini; Istiqomah Rahmawati (University of Jember, 2023)
Coffea sp. is one of the largest plantation commodities in Indonesia, especially coffee leaves containing phenolic compounds. This research was conducted to extract phenolic compounds using the Ultrasound-Assisted Extraction method with ethanol solvent, which aims to determine the optimum operating conditions of extraction and the influence of variations in amplitude, time, and ratio of solvents used. The experimental design used Design Expert 13 software with the response surface method box-Behnken design. The research variables used were amplitude variations (50%, 60%, and 70%), time (10, 20, and 30 minutes), and solvent ratios (0.1, 0.15, and 0.2 g/mL). Based on our study, these parameters affect the total phenolic content. The model equation for the total phenolic content of coffee leaves obtained is Y = 0.1349 – 0.0016 A – 0.0505 B + 0.0010 C + 0.0018 AB + 0.0043 AC – 0.0018 BC – 0.0004 A2 + 0.0178 B2 – 0.0014 C2 (R2 = 0.9758) with the optimum total phenolic content located in the 17th running of 0.209 mg GAE/g under conditions of 20 minutes, the ratio of material to solvent is 0.2 g/mL, and an amplitude of 50%.